Suppression of immunodominant antitumor and antiviral CD8+ T cell responses by indoleamine 2,3-dioxygenase. - Mateusz Rytelewski; Courtney E Meilleur; Maryam Atef Yekta; Peter A Szabo; Nitan Garg; Todd D Schell; Anthony M Jevnikar; Shayan Sharif; Bhagirath Singh; S M Mansour Haeryfar (PLoS ONE)
Indoleamine 2,3-dioxygenase (IDO) is a tryptophan-degrading enzyme known to suppress antitumor CD8(+) T cells (TCD8). The role of IDO in regulation of antiviral TCD8 responses is far less clear. In addition, whether IDO controls both immunodominant and subdominant TCD8 is not fully understood. This is an important question because the dominance status of tumor- and virus-specific TCD8 may determine their significance in protective immunity and in vaccine design. We evaluated the magnitude and breadth of cross-primed TCD8 responses to simian virus 40 (SV40) large T antigen as well as primary and recall TCD8 responses to influenza A virus (IAV) in the absence or presence of IDO. IDO(-/-) mice and wild-type mice treated with 1-methyl-D-tryptophan, a pharmacological inhibitor of IDO, exhibited augmented responses to immunodominant epitopes encoded by T antigen and IAV. IDO-mediated suppression of these responses was independent of CD4(+)CD25(+)FoxP3(+) regulatory T cells, which remained numerically and functionally intact in IDO(-/-) mice. Treatment with L-kynurenine failed to inhibit TCD8 responses, indicating that tryptophan metabolites are not responsible for the suppressive effect of IDO in our models. Immunodominant T antigen-specific TCD8 from IDO(-/-) mice showed increased Ki-67 expression, suggesting that they may have acquired a more vigorous proliferative capacity in vivo. In conclusion, IDO suppresses immunodominant TCD8 responses to tumor and viral antigens. Our work also demonstrates that systemic primary and recall TCD8 responses to IAV are controlled by IDO. Inhibition of IDO thus represents an attractive adjuvant strategy in boosting anticancer and antiviral TCD8 targeting highly immunogenic antigens.